Between Venus and Victoria John Gibson's portrait statue of the Hon. Mrs. Murray, later Countess Beauchamp - Ferrari, Roberto C. 19XX- (2018)
This article is the first to explore the commission and exhibition of British sculptor John Gibson’s Portrait Statue of the Hon. Mrs. Murray, Later Countess Beauchamp (1842-46), a work still owned by descendants of the sitter’s family at Stanford Hall in Leicestershire, England. Drawing on unpublished archival resources and contemporaneous reviews, this article reconsiders one of Gibson’s most overlooked statues both in the context of his oeuvre and polychrome sculpture, and as an example of co-creative agency in the history of nineteenth-century sculpture.